Study of Magelang Duck Farms in its Origin area around the Volcanoes Area in Magelang, Central Java - Widitya Tri Nugraha (Universitas Tidar, 2019)
This study aims to determine the description of the condition of the Magelang Duck Farms in its origin area which surrounded by Volcanoes. The data were collected by purposive sampling. Data consists of primary data and secondary data. Primary data collection through a combination of observation techniques and interviews while secondary data obtained by recording existing data and statistics derived from relevant agencies. Data were analyzed by descriptive analysis method descriptive analysis. The results showed that the prospect of re-developing Magelang ducks were met at good opportunity by looking at the condition of the Strategic District of Secang; Environmental and Humidity Conditions of Secang Subdistrict supports the development of Magelang ducks; Magelang duck housing system, feeding system is still very simple and can still be used; Magelang duck farmer human resources are still not much and have not processed yet magelang duck eggs or meat. The conclution is needed special attention so that Magelang duck farmers don't go out of business.Keywords: Magelang duck, Volcanic area condition, Sempu, Indonesia